Clinical efficacy of acupuncture for pain relief from renal colic: A meta-analysis and trial sequence analysis - Chen, Hsiao-Tien; Kuo, Cheng-Feng; Hsu, Chin-Chia; Lai, Li-Chun; Cheng, Ai-Chin; Sun, Cheuk-Kwan; Hung, Kuo-Chuan (Frontiers in Medicine, 2023)
Background This meta-analysis aimed at investigating the efficacy of acupuncture for relieving renal colic and reducing the risk of analgesic-related complications. Methods Randomized controlled trials (RCTs) comparing the efficacy of acupuncture (acupuncture group) with conventional interventions (control group) were screened from MEDLINE, EMBASE, Cochrane library databases, China Knowledge Network (CNKI), and Airiti Library till July 15, 2022. The primary outcome was the rate of effective pain relief (response rate), while secondary outcomes included the time of onset of pain relief, visual analog scale (VAS) at 30–60 min and risk of side effects. Results Thirteen eligible studies involving 1,212 participants published between 1992 and 2021 were analyzed. Compared with the control group, patients receiving acupuncture had a higher overall response rate [risk ratio (RR) = 1.12, 95% CI: 1.05–1.19, p = 0.0002, I2 = 41%, 1,136 patients] (primary outcome) and a faster pain relief [MD = −10.74 min, 95% CI: −12.65 to −8.82, p < 0.00001, I2 = 87%, 839 patients]. Patients receiving acupuncture had a lower pain score [MD = −0.65, 95% CI: −1.09 to −0.21, p = 0.21, I2 = 55%, 327 patients] and risk of side effects (RR = 0.11, 95% CI: 0.04–0.26, p < 0.00001, I2 = 0, 314 patients) compared to those receiving conventional interventions. Results from trial sequence analysis revealed sufficient evidence supporting the beneficial effects of acupuncture on response rate, time to pain relief, and pain score at 30–60 min. Conclusion Compared with conventional analgesic-based interventions, acupuncture can more efficiently relieve renal colic with fewer adverse effects. The limited number and quality of included studies warrant more clinical RCTs to support our findings. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022346714.